A review on feasibility study of ultrasonic assisted machining on aircraft component manufacturing - Saiful Bahri, Mohamed; Hafiz, M.S.A; Kawaz, M.H.A; Kasim, M.S; Izamshah, R; Saedon, J.B (2017)
Inconel 718 has been widely used in aerospace because of its excellent mechanical properties such as good corrosion resistance, strong creep resistance and high fatigue strength. However, these excellent properties also lead to heavy tool damage and high cutting force in the milling process. There is no reported investigation on ultrasonic assisted machining (UAM) of Inconel 718 parts. In this paper, UAM is proposed as the potential technique to reduce tool damage and the cutting force of Inconel 718 parts. This review paper provides an overview of UAM to investigate the relationship between the tool wear and the cutting force with ultrasonic vibration compared to without ultrasonic vibration assisted. Throughout the study, the UAM scopes are related to the tool life of coated carbide insert, the force generated during the cutting process and also the final surface finish of the workpiece by using various parameters during the machining activity.